Awareness and Compliance to Standard Precautionary Measures: A Study among Nurses at Madonna University Teaching Hospital, Elele, Rivers State - Frank, Maureen, D; Amagboruju Victoria; Robinson-Bassey, Grace.C; Ibudeh Sandra (Disease and Health Research: New Insights Vol. 8, 2024)
Standard precautionary measures (SPMs) are essential infection control practices designed to prevent the transmission of infectious agents in healthcare settings. These measures, including hand hygiene, use of personal protective equipment (PPE), and safe injection practices, are fundamental in ensuring the safety of both healthcare workers and patients. The study aimed to evaluate the awareness and compliance with standard precautionary measures among nurses at Madonna University Teaching Hospital (MUTH) in Elele, Rivers State. The investigation was guided by two research questions aligned with the study’s objectives and utilized a descriptive survey research design. The sample comprised 102 nurses from various wards and units within MUTH. Data was gathered using a self-structured questionnaire, which was validated by field experts and tested for reliability using a test-retest method, resulting in a high correlation of 0.86. Out of the 102 distributed questionnaires, 92 were returned, resulting in a 90% response rate. The data were analyzed using descriptive statistics, including frequencies and percentages. Results indicated that 89 out of 92 respondents (96.7%) demonstrated good knowledge of standard precautions, and 80 (86.96%) adhered to these measures. Statistical analysis revealed no significant relationship between years of service and compliance with standard precautions (X2 (2, .05) = 0.425), leading to the retention of the null hypothesis. The study concluded that nurses at MUTH generally possess good knowledge and compliance with standard precautionary measures. Recommendations include enhancing and supporting factors that contribute to better adherence to these protocols. The study suggests that secondary and health institutions should enhance their provision of equipment and facilities to further improve compliance with these measures.